PROSEDUR USULAN PEMBIAYAAN MODAL USAHA DANA MIKRO PT. BPR(PERSERODA) PADA MITRA USAHA PEMPEK EMBIK - Marieska Lupikawati; Afrizawati Afrizawati; Dewi Fadilah; Sari Lestari Ridho (Politeknik Negeri Sriwijaya, 2018)
The purpose of community service program is to provide solutions as a concrete step in solving business problems. The object of community service is Pempek Embik, a micro-scale businesses managed by a husband and wife. The problem of Pempek Embik was the lack of business capital since entering the fasting of Ramadan 1439 H or the end of May 2018, where prices of raw materials to make pempek rise and not decline until now. Pempek Embik has stability sales and owners of business have never made a loan because fear, not being able to pay interest. PT. BPR (perseroda) has a product with name is a credit program without guarantees and without interest. This credit is program of the Mayor of Palembang city, Mr Harnojoyo, who is committed to maximizing the potential of SMEs. The procedure for proposing credits program were three stages, first stage of completing business licenses and business recommendations from Kelurahan, second phase of data verification and business surveys and the last stage was disbursing credit program in installments of IDR 250,000 each month without interest. Pempek Embik has five working days in a week or 20 working days in a month. Pempek Embik must save IDR 12,500 for each day. With consistent and working hard, this monthly installment will be easy to do.